Coniferous Trees: Meaning, Types and Significance in Landscape Design (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article provides information about the meaning of conifers, their types, their ecological importance, specific characteristics, and natural resources obtained from these types of plants. In addition, information about its role, advantages and disadvantages in decorative gardening and landscape design is provided.